Analisis Value Chain Pada Perencanaan Sistem Informasi Sekolah Musik - Andrijana Kusuma, Kanggep; Naufal, Alman; Ratna Juwita Sari, Deassy; Agung Suburdjati, Bacilius; Maulani, Shanti (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2025)
Value chain analysis in planning a music school system can complement a company's strategy to compete in the music school business. Where action will focus on product elaboration and service processes. So in order to increase success in music school business competition, it is necessary to use value chain analysis to determine the costs associated with organizational activities from providing facilities to product design and marketing. Which can be used for decision making purposes in business strategy. The research carried out aims to obtain competitive factors such as level of integration, industry panorama, segment panorama and geographic panorama. Where it will influence decision making in the company. In this research, the author carried out observations at a music school to study data, documents, and also conducted interviews with company owners as a source of information data needed by the author. The final result of this research is a mapping of the work process at a music school, which consists of main activities and supporting activities. Value chain analysis within the scope of a business system design will be very helpful in decision making when designing Information Systems and Information Technology for music schools. The suggestion from this research is that the results of the value chain analysis are expected to contribute to the design of a business strategy. Which will greatly influence the achievement of company goals. Also helps in making company decisions on Information Systems and Information Technology planning.